Endometriosis: patient-doctor communication and psychological counselling - Wischmann, Tewes; Ditzen, Beate (Archives of gynecology and obstetrics, 2023)
The fact that endometriosis is one of the most frequent gynaecological disorders in women and girls is gradually attracting greater public and political attention. There is also substantial awareness of the disorder among German gynaecologists, albeit without sufficient “equipment” for discussing the condition with patients and providing psychological counselling. This article offers hands-on proposals for medical counselling and the discussion of relevant issues, as well as other practical tips and suggested verbalisations for use by women suffering from endometriosis (and their partners). These practical recommendations will certainly help to improve the doctor-patient relationship in the case of endometriosis. The resources mentioned below (guidebooks, websites) focus on German-language offerings only.